1998
DOI: 10.1111/1467-6486.00108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Organizational Change and Failure in the Wine Industry: An Event History Analysis

Abstract: Whether organizational change is adaptive or disruptive has been an issue among organization researchers. This paper examines the eect of organizational change on organizational failure and compares the result to previous ®ndings. To increase comparability, we replicated Delacroix and Swaminathan's (1991) format of the California wine industry study using Missouri wine industry data. Event history analysis is used to cover time-varying variables and censoring problems. Following an organizational ecology persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 24 publications
2
34
0
2
Order By: Relevance
“…The direction of this causality seems unambiguous, with a positive correlation between firm size and survival chances Ahmadjian and Robinson 2001;Kato 2010;Ramanujam 1984;Stoeberl et al 1998). For instance, Campbell et al (2008) find that Chapter 11 firms are on average ten times smaller than surviving firms.…”
Section: Sizementioning
confidence: 99%
“…The direction of this causality seems unambiguous, with a positive correlation between firm size and survival chances Ahmadjian and Robinson 2001;Kato 2010;Ramanujam 1984;Stoeberl et al 1998). For instance, Campbell et al (2008) find that Chapter 11 firms are on average ten times smaller than surviving firms.…”
Section: Sizementioning
confidence: 99%
“…Since then, numerous studies found an inverse relationship between age and failure, explained by a lack of experience, structure and stability of young firms Freeman et al, 1983). Liability of newness and its high risk of failure can also be applied to established firms that have undergone drastic changes, because these changes often disrupt established routines (Amburgey et al, 1993;Hamilton, 2006); even though change can also increase survival chances if there is higher alignment with the environment (Haveman, 1992;Stoeberl et al, 1998). Finally, with respect to organizational size, and following from the concept of the liability of smallness, it is generally agreed that failure rate decreases with increased firm size (Freeman et al, 1983;Sutton, 1987).…”
Section: Understanding Corporate Failurementioning
confidence: 99%
“…Size is strongly related to organizational performance and survival (Stoeberl, Parker, & Joo, 1998). Larger facilities command greater internal resources, including a larger administrative staff, and may be more able to accommodate environmental change through internal restructuring.…”
Section: Theory and Hypothesesmentioning
confidence: 99%